Nanocomposite sensors of polyaniline-Zn-Ag for the detection of pathogenic leptospira bacteria in environmental water - Abdullah, Huda; Yu, Jion Wei; Suppiah, Aravintha Ram; Jurait, Jamal; Yahya, Iskandar; Kamal, Noorfazila; Bejo, Siti Khairani; Othman, Mohd Hafiz Dzarfan; Fen, Yap Wing; Akhtaruzzaman, Md.; Ahmad, Md Fauzi; Yuliarto, Brian (Springer Science and Business Media LLC, 2023)
This research is focused on the fabrication of a sensitive, durable and user-friendly polyaniline-Zn-Ag (PANI-Zn-Ag) nanocomposite thin film sensor for Leptospira bacterial detection. This study focuses on the performance of different concentration ratios of PANI-Zn-Ag nanocomposite thin films. The characterization of PANI-Zn-Ag nanocomposite thin films was carried out through field-emission scanning electron microscopy (FESEM), energy-dispersive x-ray (EDX) and atomic force microscopy (AFM). The sensitivity, selectivity, repeatability and stability performance of PANI-Zn-Ag nanocomposite thin films were studied using current–voltage (I–V) curves, electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). FESEM results showed an irregular particle structure of PANI-Zn0.6-Ag0.4 with diameters ranging from 20 nm to 80 nm, with low agglomeration. AFM results showed that the PANI-Zn0.6-Ag0.4 nanocomposite thin film sensor had the highest average roughness and grain size. These specific morphological properties are required to maximize the reaction between the particles in PANI-Zn-Ag and the bacterial cells to increase the sensitivity. The repeatability and stability test showed a standard deviation range of 0.0005–0.001, which indicates that the PANI-Zn-Ag thin film sensor has high reusability. The selectivity test showed a large current gap between the deionized water test and the bacteria test. The sensitivity analysis showed that the PANI-Zn0.6-Ag0.4 nanocomposite thin film sensor had the highest sensitivity (26.2%). The results obtained confirm that the PANI-Zn-Ag nanocomposite thin film sensor has the potential for use as a biosensor for Leptospira bacterial detection.